The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1260/1747-9541.10.1.69
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Motor Skills, Gender and Relative Age Effects in Young Austrian Alpine Ski Racers

Abstract: The Relative Age Effect (RAE) refers to an over-representation of athletes born early in a selection year. The aims of this study were twofold: to test the presence of RAE depending on the gender and age in young alpine ski racers, and to test the influence of the level of physical motor skills on RAE. We investigated 989 participants of the entrance exams of three Austrian ski boarding schools, examined their birth dates and tested three different physical fitness abilities. Chi2-tests revealed significant RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
1
25
0
4
Order By: Relevance
“…Since these early studies, RAEs have been identified across a variety of team sport and cultural contexts including North American and European ice hockey [20][21][22] as well as soccer [23,24] and rugby worldwide [10,25,26]. RAEs are also documented in individual sports such as swimming [27,28], tennis [27,29,30] and Alpine skiing [31,32]. That said, RAEs are not ubiquitous as the effect has not been consistently observed in adult senior professional sport [33,34] and is absent in sports dependent on technique or skill rather than physical attributes per se (e.g., golf [35]; shooting sports [36]).…”
Section: Brief Background On Raesmentioning
confidence: 99%
“…Since these early studies, RAEs have been identified across a variety of team sport and cultural contexts including North American and European ice hockey [20][21][22] as well as soccer [23,24] and rugby worldwide [10,25,26]. RAEs are also documented in individual sports such as swimming [27,28], tennis [27,29,30] and Alpine skiing [31,32]. That said, RAEs are not ubiquitous as the effect has not been consistently observed in adult senior professional sport [33,34] and is absent in sports dependent on technique or skill rather than physical attributes per se (e.g., golf [35]; shooting sports [36]).…”
Section: Brief Background On Raesmentioning
confidence: 99%
“…Sportler, welche früh im Selektionsjahr geboren sind, haben Vorteile und werden bevorzugt selektiert. Da jedoch das Talent in einer Sportart nicht vom Geburtsmonat abhängt [17], kann davon ausgegangen werden, dass viele Talente verloren gehen, wenn vermehrt und bevorzugt relativ ältere Athleten selektiert werden [15]. Aus ethischer Sicht ist zu sagen, dass dadurch eine Diskriminierung von jungen, talentierten Kindern besteht, da diese trotz ihres Talents und ihrer Anstrengungen nur geringe Chancen haben, das Elitelevel zu erreichen [15,16].…”
Section: Discussionunclassified
“…Da jedoch das Talent in einer Sportart nicht vom Geburtsmonat abhängt [17], kann davon ausgegangen werden, dass viele Talente verloren gehen, wenn vermehrt und bevorzugt relativ ältere Athleten selektiert werden [15]. Aus ethischer Sicht ist zu sagen, dass dadurch eine Diskriminierung von jungen, talentierten Kindern besteht, da diese trotz ihres Talents und ihrer Anstrengungen nur geringe Chancen haben, das Elitelevel zu erreichen [15,16]. Die zugrundeliegenden Mechanismen des RAE wurden des Öfteren untersucht; jedoch sind diese meistens, wie beispielsweise im alpinen Skirennlauf, weiterhin unbekannt und sollten deshalb erhoben werden.…”
Section: Discussionunclassified
“…Los resultados obtenidos en el Test de Harre demostraron la importancia de la capacidad de coordinación dinámica general dentro del esquí alpino infantil habiendo presentado valores superiores a los de jóvenes deportistas de otras disciplinas, en ambos sexos. Este hecho coincide con los resultados obtenidos en estudios más recientes con el mismo test (Müller et al, 2015b;Steidl-Müller et al, 2017). Estos estudios confirman que esta capacidad motora no se ve afectada significativamente por la maduración en niños y la existencia de diferencias altamente significativas a los 11 años, dentro del intervalo comprendido entre los 12 y 14 años, en niñas.…”
Section: Discussionunclassified
“…Journal of Physical Education and Human Movement, 1(2) 16-36. ISSN: 2659-5699 DOI: 10.24310/JPEHMjpehm.v1i2.6394 relativa en esquiadores adultos (Bosco, 1994(Bosco, , 1997Ruiz de Almirón et al, 2002;Raschner et al, 2008Raschner et al, , 2013Müller et al, 2015b;Steidl-Müller et al, 2017, 2019. Esto demostró que esta capacidad requiere niveles de fuerza explosiva y reactiva elevados durante los cambios de dirección en el esquí durante la bajada.…”
Section: Discussionunclassified